Aprovechamiento de los residuos de la industria maderera en la elaboracion de sustratos para la germinacion de plantas de cacao - Vacacela Belduma, Willian Alexander (2015)
In Santa Inés farm research on the use of waste timber for preparing sawdust-based substrates laurel and cinnamon in different mixes with fresh earth and sand was carried out to improve the texture on the substrate and that in this way can help the growth of cocoa seedlings CCN - 51. The objectives were: 1. Check the use of wood waste as a substrate for the arrest of cocoa seedlings, 2. Evaluate the initial development of seedlings.The study area corresponds to a Tropical (bms-T) very dry forests with an annual rainfall of 699 mm, with an average annual temperature of 25 ° C and a relative humidity of 84%. T1 investigated treatments sand, sweet land T2, T3 sand - sweet land, sweet land T4 - sawdust bay, sand T5 - sawdust laurel, sweet land T6 - sawdust cinnamon, bay sawdust T7 - sand - cinnamon sawdust - sweet land. The experimental design was a completely randomized design with seven treatments and four repetitions, the variables studied were: Days to seed germination cocoa number of days to the fall of the cotyledons, plant height at 30, 45 and 60 days Number of sheets 30, 45 and 60 days, leaf area at 45 and 60 days and root length at 60 days. The seed without testa was the proceeded to plant in each of the corresponding treatments.In days Variable seed germination, reading occurs without replicas because it is a point estimate which their respective average with standard deviation is presented. Sweet Land Treatment T4 - T5 sawdust and sand bay - laurel sawdust showed better results for their precocious germination. 2In the analysis of variance for height 30 days high statistical significance was obtained which showed that the sand T5 - sawdust bay if influenced up to 30 days of seedlings. The root growth and the leaf emergence and leaf area were not statistically significant.